Determination of organic acid impurities in lactic acid obtained by fermentation of sugarcane juice - Qureshi, Mohd Shadbar; Bhongale, Sunil Sitaram; Thorave, Archana K. (Journal of Chromatography A, 2011)
Lactic acid produced by fermentation process mostly contains a number of aliphatic carboxylic acids as impurities. In this work, carboxylic acid impurities in lactic acid samples from a number of sources were determined at ppm levels. A simple HPLC method was developed that utilized a new generation polar embedded reverse phase, 20 mM phosphate buffer at pH 2.20 (+/- 0.05) and UV detection at 210 nm. The method enabled quantitative analysis of the above acids in lactic acid matrix. The experimental conditions for column temperature, mobile phase pH and flow rate were optimized. A detailed validation of the method was performed for linearity, precision, accuracy, selectivity, limit of detection (LOD), limit of quantitation (LOQ), ruggedness and repeatability and reproducibility (R&R). (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Lactic acid; Method validation; Organic acid impurities; Polar embedded RP-HPLC; Sugarcane juice fermentation